2014
DOI: 10.1155/2014/730380
|View full text |Cite
|
Sign up to set email alerts
|

The Treg/Th17 Paradigm in Lung Cancer

Abstract: Pathogenic mechanisms underlying the development of lung cancer are very complex and not yet entirely clarified. T lymphocytes and their immune-regulatory cytokines play a pivotal role in controlling tumor growth and metastasis. Following activation by unique cytokines, CD4+ T helper cells differentiate into Th1, Th2, Th17, and regulatory T cells (Tregs). Traditionally, research in lung cancer immunity has focused almost exclusively on Th1/Th2 cell balance. Recently, Th17 cells and Tregs represent an intriguin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 113 publications
2
62
0
Order By: Relevance
“…CD4 + CD25 + FOXP3 + Tregs account for 5-10% of all T lymphocytes in healthy individuals (23). Evidence suggests that Tregs contribute to immune suppression by dampening the antitumor immunity elicited by CD4 + T cells, CD8 + T cells, dendritic and NK cells (24)(25)(26)(27). Treg accumulations in tumors and peripheral blood have been linked to unfavorable disease outcomes of tumor invasion, recurrence and shortened survival for many human solid tumors, including hepatocellular carcinoma, ovarian carcinoma, pancreatic ductal carcinoma, cervical cancer, NSCLC and breast cancer (28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…CD4 + CD25 + FOXP3 + Tregs account for 5-10% of all T lymphocytes in healthy individuals (23). Evidence suggests that Tregs contribute to immune suppression by dampening the antitumor immunity elicited by CD4 + T cells, CD8 + T cells, dendritic and NK cells (24)(25)(26)(27). Treg accumulations in tumors and peripheral blood have been linked to unfavorable disease outcomes of tumor invasion, recurrence and shortened survival for many human solid tumors, including hepatocellular carcinoma, ovarian carcinoma, pancreatic ductal carcinoma, cervical cancer, NSCLC and breast cancer (28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…T reg s, whose activation is under control of CTLA-1 checkpoint, have the specific ability to attenuate the extent of cancer associate immuneresponse and represents a common mechanism of immuneescape for cancer cells (26)(27)(28)(29). IL-17A is able to promote A B the switch of inactive T reg s in highly suppressive subsets that, in turn, can inhibit all the attempts of immune-system and tumor-specific CTLs to counteract tumor growth and development (29)(30)(31)(32) another very active CTL subset expressing the L selectin (CD62L), a trans-membrane protein which allows the binding to the specific receptor on tumor vessels and the consequent extravasation in the tumor sites (37). In our patients, we also found a significant increase of peripheral DCs expressing CD83 and CD80, a very efficient antigen presenting cell linage able to uptake and process antigen released by tumor tissues exposed to the cytotoxic drugs (38).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, CD4+ T cells, differentiating into Th2 cells, express GATA3 and Stat6 and produce more IL-4, IL-5, and IL-13. In addition, CD4+ Th2 cells are part of a type-2 immune response, i.e., a type of immunity which is mainly involved in the removal of helminthes and extracellular parasites and facilitates B-cell antibody secretion (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have progressively revealed the role of recently recognized CD4+ subsets, i.e., Th17 cells and T regulatory cells (Tregs), in immunity, particularly at mucosal surfaces where large and diverse numbers of microbes (also known as microbiomes) reside (5,6). Th17 cells, as an inflammatory subset of CD4+ cells, are the main source of IL-17A, IL-17F, and IL-22 (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation